2020
DOI: 10.1101/2020.07.13.20150177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a severity of disease score and classification model by machine learning for hospitalized COVID-19 patients

Abstract: BACKGROUND: Efficient and early triage of hospitalized Covid-19 patients to detect those with higher risk of severe disease is essential for appropriate case management. METHODS: We trained, validated, and externally tested a machine-learning model to early identify patients who will die or require mechanical ventilation during hospitalization from clinical and laboratory features obtained at admission. A development cohort with 918 Covid-19 patients was used for training and internal validation, and 352 pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…A total of 20 studies were included in the qualitative and quantitative synthesis ( Fig. 1 , Table 1 ) [ 2 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. One study which we included described an OR value.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies were included in the qualitative and quantitative synthesis ( Fig. 1 , Table 1 ) [ 2 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. One study which we included described an OR value.…”
Section: Resultsmentioning
confidence: 99%
“…Table S4). In quantitative analysis, 10 studies were excluded as seven [21][22][23][24][25][26][27] only reported Pvalue and three [28][29][30] reported different effect measures.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Some research have tried to study the use of AI approaches in identifying covid-19 cases via these data. Using the clinical and laboratory features obtained at admission, a machine learning algorithm is proposed in [113] which predicts if patients require mechanical ventilation or will die or survive when hospitalized. In order to evaluate the early risk assessment for patients, in [114] demographic data, physiological clinical variables and laboratory results from electronic healthcare records are extracted and used with applied multivariate logistic regression, random forest and extreme gradient boosted trees.…”
Section: Clinical Applicationsmentioning
confidence: 99%